DESIGN OF DATA MINING METHOD IN MAKING INTELLIGENT RESULTS REPORT TO PREVENT CRIMINAL ACTS OF TERRORISM IN THE SEMARANG IMMIGRATION OFFICE - Y. Edo Budi Prasetyo (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
The events of September 11 in the United States changed the world's understanding of terrorism. Terrorism is now understood as a transnational event. Countries in the world are trying to ratify legal instruments on the prevention and suppression of terrorism. Indonesia as a country that requires income from international migration events requires immigration to play an active role in preventing terrorism. With the rapid development of technology, data mining techniques on social media can be utilized to carry out cyber intelligence. This study aims to determine data mining techniques on social media twitter to prevent terrorism. This research uses descriptive qualitative research methods with the help of the socio-psychological narcissistic theory, intelligence, and data mining. The analysis was performed using data reduction techniques. This study will explain how data mining techniques on social media can be used to create immigration intelligence reports. This research is expected to be applied to the making of daily intelligence reports at the Semarang Immigration Office.